STATE STIMULATION OF INNOVATIVE INFRASTRUCTURE DEVELOPMENT IN THE REGION - A. Nikonorova (Вестник университета)
The article reveals the questions of state stimulation of innovative activity in the region. The analysis of normative and legislative documents in the field of economic activity regulation of domestic enterprises operating on the Black Sea region is made. The article also highlights the most important and perspective directions of state stimulation in development of innovative infrastructure of the region. Special attention is paid to implementation of target programs and their impact on improving quality of provided services and standard of living of resident population.